Evaluasi Konsumsi Nasi Sagu terhadap Parameter Gizi dan Biokimia pada Responden dengan Berat Badan Berlebih dan Kegemukan: An Evaluation of Sago-Rice Consumption on Nutritional and Biochemical Parameters in Overweight and Obese Participants - Aji, Galih Kusuma; Hariyanto, Bambang; Pangestu, Alit; Kusumasmarawati, Ambar Dwi; Cahyana, Purwa Tri (Amerta Nutrition, 2025)
Background: Overweight and obesity are conditions caused by overnutrition, where an individual has an excessive nutrient intake. These conditions can lead to blood glucose and lipid problems. Sago rice, rich in resistant starch and fiber, offers a potential solution to this issue. Objectives: This study aimed to investigate the impact of eating sago rice over 4 weeks on the biochemical (glucose, total cholesterol, and triglyceride) and nutritional (body weight, Body Mass Index (BMI), total fat, and visceral fat contents) parameters in overweight and obese participants. Methods: Each participant consumed approximately 200 g of sago rice during lunch for 4 weeks. The researchers measured the participants’ body weight and height, which were then used to calculate their BMI before and after consuming the sago rice. They also performed Bioelectrical Impedance Analyses (BIA) to calculate the participants’ body and visceral fat percentages before and after consumption. The participant’s total cholesterol and triglycerides were also examined before and after the sago-rice consumption using the spectrophotometry method. Results: After 4 weeks of sago-rice consumption, the results highlighted a significant decrease in body weight, BMI, and body fat percentage (p-value<0.05). This study demonstrated that consuming sago rice for 4 weeks could significantly decrease the participants’ total cholesterol levels by approximately 18 mg/dL, from 257.33 mg/dL to 239.48 mg/dL (p-value<0.05). Conversely, the participants’ triglyceride levels increased (p-value<0.05). However, blood glucose concentration was not significantly different (p-value>0.05). Conclusions: Therefore, sago rice consumption can help reduce body weight, BMI, body fat percentage, and total cholesterol levels in overweight and obese individuals.